How television ratings work - Jankowski, Laurence; Instructional Video (Firm); First Light Video Publishing (USA : Instructional Video; Venice, CA. : First Light Video Publishing (distributor), 2006)
Describes how television ratings are determined by using randomly selected households across America. Shows how sampling takes place and how homes are selected to participate
Title from title screen
Keywords: Television programs -- Rating; Television